(Please Don't) Say It to My Face! The Interaction of Feedback and Distance: Experiments with Vulgar Language. (May 2016) - Johnson, David Blake
Summary: I extend current understanding of non‐monetary punishments by introducing one‐way unrestricted feedback (vulgar language) from responders in laboratory and online ultimatum games. Feedback changes in the expected direction. Negative feedback is returned in the event of low offers while higher offers receive positive feedback. Additionally, the possibility of unrestricted feedback significantly increases amounts sent by proposers, but only in the lab. This effect is statistically significant and large in magnitude but is not present in the online experiments. These results illustrate that increases in social distance and/or physical proximity can weaken the effectiveness of non‐monetary punishments.